Epigenetic modification of hypothalamic neuropeptides and metabolic hormone receptors in metabolic health - Oladun, Busayo; Mall, Smita; Kim, Min-Hyun (Frontiers in Endocrinology, 2025)
The hypothalamus plays a central role in regulating metabolism by integrating neuropeptide signaling with environmental cues to maintain energy homeostasis. Adverse environmental factors, such as obesogenic diet, undernutrition, stress, and sedentary lifestyles, can disrupt the normal regulation of key hypothalamic neuropeptides and metabolic hormone receptors through epigenetic mechanisms, including DNA methylation, histone modifications, and microRNA regulation. These epigenetic alterations are not merely transient; they can be heritable and may influence metabolic health across generations, highlighting the critical need to understand the underlying epigenetic mechanisms. In this review, we provide a comprehensive overview of how environmental factors shape the epigenetic landscape of hypothalamic neuropeptides (pre-opiomelanocortin, neuropeptide Y, and agouti-related peptide) and metabolic hormone receptors (leptin receptor and insulin receptor), thereby modulating their expression and contributing to long-term metabolic outcomes. A better understanding of environment-epigenome interactions holds promise for the development of innovative therapeutic strategies to combat obesity and metabolic disorders.